2021
DOI: 10.1002/ajp.23230
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pelage, background, and distance on predator detection and the evolution of primate color vision

Abstract: Primates' predators, such as carnivore mammals, usually rely on camouflage to increase proximity to prey and start a predatory attempt. Camouflage depends not only on the color pattern presented by a predator's pelage but also on the background scene in which the hunting takes place. Another factor that influences camouflage effectiveness is prey's color vision since a given camouflage strategy might not work for all visual phenotypes. Still, little research has been made on the effect of primate visual phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 95 publications
(168 reference statements)
1
19
0
Order By: Relevance
“…Color information could therefore contribute, albeit slightly, to the rapid categorization of snakes, as it does for faces that are also highly relevant stimuli for the survival of the species ( Or et al, 2019 ). This observation echoes recent findings that trichromat humans—as are most representatives of our species by 3 months ( Teller, 1998 )—outperform dichromats in detecting predators ( Pessoa et al, 2014 ; de Moraes et al, 2021 ). These findings have been taken as evidence in favor of the trichromatic advantage for predator detection hypothesis ( Pessoa et al, 2014 ) according to which trichromatic color vision evolved in humans and closely related primates due to its evolutionary advantage in detecting predators.…”
Section: Discussionsupporting
confidence: 90%
“…Color information could therefore contribute, albeit slightly, to the rapid categorization of snakes, as it does for faces that are also highly relevant stimuli for the survival of the species ( Or et al, 2019 ). This observation echoes recent findings that trichromat humans—as are most representatives of our species by 3 months ( Teller, 1998 )—outperform dichromats in detecting predators ( Pessoa et al, 2014 ; de Moraes et al, 2021 ). These findings have been taken as evidence in favor of the trichromatic advantage for predator detection hypothesis ( Pessoa et al, 2014 ) according to which trichromatic color vision evolved in humans and closely related primates due to its evolutionary advantage in detecting predators.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it can prolong foraging [ 22 ], reduce social harassment, or facilitate hidden copulations [ 23 ]. While it is usually prey that camouflages to avoid predation, predators also camouflage to get close to prey [ 24 ] or avoid mobbing [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…or during intraspecific communication [56][57][58][59][60]. Despite the high number of research investigating the environmental factors that may have influenced primate colour vision evolution, only three studies experimentally evaluated the importance of predation risk on this matter to date [33,61,62]. Several studies have shown that the effectiveness of a camouflage strategy depends on the visual system that observes it [14,33,[63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%